Φ-Admissible Sublinear Singular Operators and Generalized Orlicz-Morrey Spaces. (3rd December 2013) - Hasanov, Javanshir J.
Abstract : We study the boundedness ofΦ -admissible sublinear singular operators on Orlicz-Morrey spacesM Φ, φ ℝ n . These conditions are satisfied by most of the operators in harmonic analysis, such as the Hardy-Littlewood maximal operator and Calderón-Zygmund singular integral operator.